2017
DOI: 10.1158/0008-5472.can-17-0064
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C and Integrin α9 Mediate Interactions of Prostate Cancer with the Bone Microenvironment

Abstract: Deposition of the extracellular matrix protein tenascin-C is part of the reactive stroma response, which has a critical role in prostate cancer progression. Here, we report that tenascin C is expressed in the bone endosteum and is associated with formation of prostate bone metastases. Metastatic cells cultured on osteo-mimetic surfaces coated with tenascin C exhibited enhanced adhesion and colony formation as mediated by integrin α9β1. In addition, metastatic cells preferentially migrated and colonized tenasci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 56 publications
6
63
0
Order By: Relevance
“…Seven hub genes ( VCAN , COL3A1 , COL1A1 , APOE , COL1A2 , SDC1 and THY1 ) with worse BCR‐free survival and one hub gene ( MMP9 ) with worse OS were detected. The 20 hub genes were enriched in extracellular matrix, cell‐substrate adhesion, integrin, collagen and mesenchymal cell differentiation, which played a vital role in bone metastasis [22–26]. MCODE can find molecular complexes in the PPI network.…”
Section: Discussionmentioning
confidence: 99%
“…Seven hub genes ( VCAN , COL3A1 , COL1A1 , APOE , COL1A2 , SDC1 and THY1 ) with worse BCR‐free survival and one hub gene ( MMP9 ) with worse OS were detected. The 20 hub genes were enriched in extracellular matrix, cell‐substrate adhesion, integrin, collagen and mesenchymal cell differentiation, which played a vital role in bone metastasis [22–26]. MCODE can find molecular complexes in the PPI network.…”
Section: Discussionmentioning
confidence: 99%
“…TN-C has been shown to stimulate proliferation and survival in a variety of cancers by activating several pathways downstream of integrins and syndecans(135), including integrin α9β1 activation of Akt and MAPK(136) and αvβ3 activation of FAK and paxillin(137). However, a recent study showed that TN-C signaling through integrin α2β1, but not α9β1 or αvβ3, induced autocrine growth in brain tumor cells(138). Through an indirect mechanism of tumorigenesis, TN-C is able to compete with syndecan-4 binding to fibronectin, thereby interfere with fibronectin inhibition of proliferation(139).…”
mentioning
confidence: 99%
“…In the same paper, the authors also showed correlation of drug responses in the established in vitro model and an in vivo bone metastasis model [40]. The novel use of the chorioallantoic membrane (CAM) model in the context of prostate cancer invasion and bone metastasis is also an interesting addition to the model portfolio [41]. In this assay, a bone chip is placed on top of the CAM and cancer cells are injected a small distance away from the bone, from where they can then invade and colonize the bone [41].…”
Section: Other Models Related To Bone Metastasismentioning
confidence: 88%
“…The novel use of the chorioallantoic membrane (CAM) model in the context of prostate cancer invasion and bone metastasis is also an interesting addition to the model portfolio [41]. In this assay, a bone chip is placed on top of the CAM and cancer cells are injected a small distance away from the bone, from where they can then invade and colonize the bone [41]. In many ways, this model settles in between the in vitro assays and mouse models.…”
Section: Other Models Related To Bone Metastasismentioning
confidence: 99%